2021
DOI: 10.1142/s0219649221400074
|View full text |Cite
|
Sign up to set email alerts
|

Internet of Things Infrastructures in Academic Libraries: A Case Study in Iran

Abstract: Internet of Things (IoT) is going to create many changes in libraries. However, its application in libraries requires the use of various infrastructures. This paper aims to determine IoT infrastructures in academic libraries and examine them in Iranian academic libraries. This is a descriptive survey with two qualitative and quantitative approaches. The statistical population consists of 15 central libraries of state universities of Tehran in 2018. The infrastructures needed to apply this technology in librari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 17 publications
3
10
0
Order By: Relevance
“…Effective change management strategies are intensely needed for the successful adoption and sustainability of IoT-based library systems and services in universities. Similar challenges were reported by Asim et al (2022), Chen and Hao (2022), Harati et al (2021), Hoy (2015), Igbinovia and Okuonghae (2021), Makori (2017), Muhamad and Darwesh (2020) and Osman et al (2023) in their studies.…”
Section: Adoption Of Internet Of Thingssupporting
confidence: 89%
See 1 more Smart Citation
“…Effective change management strategies are intensely needed for the successful adoption and sustainability of IoT-based library systems and services in universities. Similar challenges were reported by Asim et al (2022), Chen and Hao (2022), Harati et al (2021), Hoy (2015), Igbinovia and Okuonghae (2021), Makori (2017), Muhamad and Darwesh (2020) and Osman et al (2023) in their studies.…”
Section: Adoption Of Internet Of Thingssupporting
confidence: 89%
“…Effective usage of library resources is ensured through IoT adoption in university libraries. Required information resources are provided to the end users in the required format (Harati et al, 2021;Kumar, 2018). Library services are improved and users' information and research needs are addressed through smart methods (Khan et al, 2022).…”
Section: Adoption Of Internet Of Thingsmentioning
confidence: 99%
“…Large wireless system capacity, simplified network planning and setup, interoperable architecture, remote network and device management and a flexible and scalable software infrastructure are essential factors for building IoT-based services (Behrtech, 2020). The infrastructural issues including technological, financial, and human resources should be the prime considerations for the university libraries of Bangladesh in order to capitalize the potential benefits of IoT, which are consistent with the findings of Harati et al. (2021).…”
Section: Discussionsupporting
confidence: 59%
“…Despite the opportunities of IoT, some studies identified a number of challenges of implementing IoT technology in libraries (Asim and Arif, 2023;Asim et al, 2022;Harati et al, 2021;Igbinovia and Okuonghae, 2021a;Bansal et al, 2018;Kaba and Ramaiah, 2019;Kumar, 2016;Hoy, 2015). As there is no standard for this technology, it can exchange data using multiple companies' own parameter and thus the risk of unauthorized access and system hacking would be a common issue (Hoy, 2015).…”
Section: Challenges Of Iot Adoption In Librariesmentioning
confidence: 99%
See 1 more Smart Citation